Pediatric pressure injuries: A systematic review of interventions to prevent hospital-acquired pressure injuries in the pediatric population - Bauernfeind, Lydia; Rester, Christian; Schoenstein, Stefan (Kontakt, 2024)
Introduction: Pressure injuries have been identified as a problem in adults, but there is increasing recognition that they also occur in pediatric patients. Specific prevention in this population is essential because a high percentage of pressure injuries can be prevented. Objective: To identify interventions that prevent pressure injuries in the clinical pediatric care setting. Methods: Systematic review with a conducted search in CINAHL, PubMed, and Cochrane databases. A total of 301 articles were found, 225 were excluded after reviewing the title and abstract. The remaining papers were subjected to a full-text screening. Eligible studies were those that (a) described interventions to prevent pressure injuries, (b) were specifically aimed at pediatric patients (0-18 years), (c) were published in English or German, and (d) were conducted in a hospital. Results: A total of 37 studies were included. The data on interventions from the studies were extracted and clustered. The following eight categories of interventions for the prevention of pressure injury in pediatric patients were identified: (1) (Skin)Assessments, (2) Medical devices, (3) Positioning, (4) Education, (5) Moisture Management, (6) Nutrition Management, (7) Surfaces, and (8) Intervention bundles. The included studies described various interventions for pressure injury prevention. Most reported a significant reduction in pressure injury rates when intervention bundles were implemented. Conclusion: Nurses have to know about pressure injury causation, risk factors, and prevention strategies to implement the identified interventions and prevent pressure injuries in pediatric patients during hospital stays.
Keywords: Pressure Ulcer; péče o kůži; kontinuální vzdělávání zdravotních sester; Skin Care; Patient Positioning; Education, Nursing, Continuing; lidé; dítě hospitalizované; Child, Hospitalized; Nursing Care; ošetřovatelská péče; polohování pacienta; dekubity; Humans